Fasting induces the expression of PGC-1α and ERR isoforms in the outer stripe of the outer medulla (OSOM) of the mouse kidney. - Christina T Teng; Yin Li; Pat Stockton; Julie Foley (PLoS ONE)
Background Peroxisome proliferator-activated receptor-γ co-activator-1α (PGC-1α) is a member of the transcriptional coactivator family that plays a central role in the regulation of cellular energy metabolism under various physiological stimuli. During fasting, PGC-1α is induced in the liver and together with estrogen-related receptor a and γ (ERRα and ERRγ, orphan nuclear receptors with no known endogenous ligand, regulate sets of genes that participate in the energy balance program. We found that PGC-1α, ERRα and ERRγ was highly expressed in human kidney HK2 cells and that PGC-1α induced dynamic protein interactions on the ERRα chromatin. However, the effect of fasting on the expression of endogenous PGC-1α, ERRα and ERRγ in the kidney is not known. Methodology/principal findings In this study, we demonstrated by qPCR that the expression of PGC-1α, ERRα and ERRγ was increased in the mouse kidney after fasting. By using immunohistochemistry (IHC), we showed these three proteins are co-localized in the outer stripe of the outer medulla (OSOM) of the mouse kidney. We were able to collect this region from the kidney using the Laser Capture Microdissection (LCM) technique. The qPCR data showed significant increase of PGC-1α, ERRα and ERRγ mRNA in the LCM samples after fasting for 24 hours. Furthermore, the known ERRα target genes, mitochondrial oxidative phosphorylation gene COX8H and the tricarboxylic acid (TCA) cycle gene IDH3A also showed an increase. Taken together, our data suggest that fasting activates the energy balance program in the OSOM of the kidney.